Akibat Hukum Batalnya Permohonan Pendaftaran Hak Tanggungan Elektronik menurut Peraturan Menteri ATR/BPN Nomor 5 Tahun 2020 - I Made Yoga Bisama; Anak Agung Istri Agung; Desak Gde Dwi Arini (Warmadewa Press, 2022)
The president cannot regulate all areas of government independently, the government is formed such as the National Land Agency to create a land system in Indonesia. The land sector is related to Mortgage Rights because it is important where banks as creditors to the public need capital with objects being used as collateral by debtors. Technological advances brought changes, previously Mortgage was registered manually which was complicated and convoluted then gave rise to Electronic Mortgage Registration. The purpose of this research is to analyze the process of completing the cancellation of electronic mortgage registration according to the Minister of ATR/BPN Regulation Number 5 of 2020, and to understand the legal consequences of the cancellation of an electronic mortgage registration application according to the Regulation of the Minister of ATR/BPN Number 5 of 2020. The research method used is a type of empirical research using a sociological approach. The sources of legal materials for this research are primary and secondary sources. Data collection techniques used interview techniques, and recorded and documented data materials. This research discusses the process of completing the cancellation of registration and the legal consequences of canceling the application for registration of electronic mortgages according to the Minister of ATR/BPN Regulation Number 5 of 2020. The results of this research indicate that the settlement process in the event of cancellation of Electronic Mortgage Rights is by completing the conditions stipulated in Article 1 paragraph (1) Regulation of the Minister of Agrarian Affairs Number 5 of 1996 and the Legal Consequences of the Cancellation of the Application for Electronic Mortgage Rights, the debtor registers and pays PNBP again.